Molecular Insights into CO2 Sequestration in MOF-74 - Subedi, Anup; Adhikari, Bishwas; Bhusal, Aabiskar; Adhikari, Kapil (Journal of Institute of Science and Technology, 2024)
Advancements in materials for efficient carbon sequestration are crucial in addressing the rising levels of CO₂. Metal Organic Frameworks (MOFs) have emerged as a key focus due to their high CO₂ absorption capacity and versatility. This study focuses on evaluating the equilibrium CO₂ adsorption properties of Mg-MOF-74 using hybrid MD / GCMC simulation in LAMMPS. The simulations were conducted at a temperature of 313 K with pressure variations ranging from 1 to 40 bar. The resulting CO₂ uptake was 10.185 mmol/g even at a low pressure of 1 bar. As pressure increases, CO₂ adsorption steadily rises, reaching 12.810 mmol/g at 40 bar. The Radial Distribution Function (RDF) analysis of CO₂ molecules within Mg-MOF-74 clarified the significant role of ligands in CO₂ adsorption. The observed decrease in the diffusion coefficient with increasing pressure suggests slower diffusion and indicates a strong interaction between CO₂ and the MOF at higher pressures. Moreover, the increasingly negative trend of interaction energy with rising pressure indicates enhanced adsorption at higher pressures, with van der Waals interactions contributing predominantly to the total interaction energy between adsorbate and adsorbent. This research sheds light on the potential of Mg-MOF-74 as an effective material for CO₂ capture and sequestration.